Analysis of the Relationship Between Military Expenditure and Investment in the Economic Community of West African States: a Heterogeneous Panel Data Approach - Efayena, Obukohwo Oba; Olele , Enoh Hilda (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2024)
West Africa has been grappling with various security challenges prompting governments’ intervention via military expenditure both at the country and regional level. Given the sporadic surge in military expenditure in the region and the potential effect such expenditure may exert on investment which is a sin qua non to the development process of any economy or region, this study utilizes the augmented mean group (AMG) approach and the Granger non-causality test in investigating the impact and causal relationship between investment and military expenditure in the Economic Community of West African States (ECOWAS) between 1980 and 2020. With country-specific cross-dependence and heterogeneity adequately accounted for, the study found that military expenditure has a dampening impact on investment at both the panel and country levels; unemployment adversely impacts investment; whereas economic growth stimulates investment (catalytic effect) in the ECOWAS, although at differing levels of significance. The study also established a long-run relationship among the variables; with only economic growth Granger causing investment. The study thus recommends that country-specific and regional-based military policies be established to glean economic growth through viable investment.